1990
DOI: 10.1037/0735-7044.104.6.964
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral connections of the medial preoptic area and maternal behavior in rats.

Abstract: The lateral connections of the medial preoptic area (MPOA) are essential for maternal behavior in rats. The purpose of this study was to more exactly specify the nature of this pathway. Experiment 1 found that knife cuts that severed the dorsolateral connections of the MPOA were as effective as complete cuts in disrupting maternal behavior, whereas knife cuts that severed the ventrolateral MPOA connections were ineffective. These results suggest that MPOA efferents and afferents critical for maternal behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…In addition, this study identified no specific molecular expression that closely corresponded with c-Fos-ir neurons in the cMPOA, although the distribution of Vglut2 mRNA was most prominent in the cMPOA. Because the dorsolateral MPOA was suggested as the most important area for maternal behavior in rats (Jacobson et al, 1980;Numan et al, 1990;Numan and Numan, 1996;Kalinichev et al, 2000), some interspecific difference might exist in the relative location of the essential subregion within MPOA for maternal behavior between mice and rats. Because cMPOA consists of heterogeneous neurons, our point is not contradictive of the previous delineation in the MPOA and adjacent areas, which might match some kinds of molecular expression and/or projection patterns.…”
Section: Molecular Features Of Cmpoa Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, this study identified no specific molecular expression that closely corresponded with c-Fos-ir neurons in the cMPOA, although the distribution of Vglut2 mRNA was most prominent in the cMPOA. Because the dorsolateral MPOA was suggested as the most important area for maternal behavior in rats (Jacobson et al, 1980;Numan et al, 1990;Numan and Numan, 1996;Kalinichev et al, 2000), some interspecific difference might exist in the relative location of the essential subregion within MPOA for maternal behavior between mice and rats. Because cMPOA consists of heterogeneous neurons, our point is not contradictive of the previous delineation in the MPOA and adjacent areas, which might match some kinds of molecular expression and/or projection patterns.…”
Section: Molecular Features Of Cmpoa Neuronsmentioning
confidence: 99%
“…Although several brain areas are important for different parental behavior components (Febo, 2011;Pereira and Morrell, 2011;Stolzenberg and Numan, 2011), the medial preoptic area (MPOA) has been shown to be the most critical, especially for pup retrieval, as shown by the following four lines of evidence: first, destruction of MPOA with either electrical or excitotoxic lesions disrupts both established maternal behavior in postpartum females (Numan, 1974;Jacobson et al, 1980;Numan et al, 1988) and the onset of parental behavior in adult females (Numan et al, 1977;Fleming et al, 1983), adult males, and juveniles (Rosenblatt et al, 1996;Sturgis and Bridges, 1997;Kalinichev et al, 2000;Oxley and Fleming, 2000;Lee and Brown, 2002). Knife cuts of dorsolateral connections of the MPOA also abolish the maternal behavior of postpartum rats (Terkel et al, 1979;Numan and Callahan, 1980;Numan et al, 1990) and hamsters (Miceli and Malsbury, 1982). Additionally, temporary inactivation of MPOA neurons using GABA agonists or bupivacaine injection produces deficits in all components of maternal behavior in rats at least during the early postpartum period (Arrati et al, 2006;Pereira and Morrell, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BNST and MPOA, from which neurons project to the VTA [12][13][14], are also regulated by those hormones during pregnancy, and are critical for maternal behavior [15,16]. There is also reciprocal innervation between the BNST and MPOA, and lesions to the lateral connection between the BNST and MPOA disrupt maternal behavior [18]. Although interactions between the BNST and MPOA are required for maternal behavior, neural pathways connecting them have not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The MPOA is also involved in the parental behavior of sheep [14] and presumably most other mammals. Severing the lateral, in particular the dorsolateral, connections of the MPOA disrupts maternal behavior most strongly and specifi cally, compared to cutting the anterior, posterior, or dorsal connections [15,16] . These findings are consistent with the fact that the major afferent and efferent connections of the rat medial preoptic nucleus, the largest and central nucleus of the MPOA, enter and leave laterally [17] .…”
mentioning
confidence: 99%